Proceedings 2007 IEEE International Conference on Robotics and Automation 2007
DOI: 10.1109/robot.2007.363829
|View full text |Cite
|
Sign up to set email alerts
|

&#x003BC;<sup>3</sup>: Multiscale, Deterministic Micro-Nano Assembly System for Construction of On-Wafer Microrobots

Abstract: One of the major issues enduring with microscale mechanics has been to design high fidelity miniature machines capable of performing complex operations. Though achieved in some proportion through conventional in-plane and out-of-plane designs, the efficacy of such micro-electromechanical systems (MEMS) structures is highly limited due to complicate fabrication and inadequate robustness. On the other hand, the use of precise robots to assemble MEMS parts of comparatively simpler design to build 3D micromechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 12 publications
(12 reference statements)
0
43
0
Order By: Relevance
“…Due to variability in gripper designs and fabrication, it is currently necessary to repeat this step every time a new MEMS gripper is mounted on M 1 . A summary of techniques for mounting MEMS grippers and program the RCR can be found in Das et al [4] and Mayyas et al [13].…”
Section: Calibration Step 1: M 1 End-effector Calibration Of the Remomentioning
confidence: 99%
“…Due to variability in gripper designs and fabrication, it is currently necessary to repeat this step every time a new MEMS gripper is mounted on M 1 . A summary of techniques for mounting MEMS grippers and program the RCR can be found in Das et al [4] and Mayyas et al [13].…”
Section: Calibration Step 1: M 1 End-effector Calibration Of the Remomentioning
confidence: 99%
“…7), a 3D microassembly station consisting of 19 DOF arranged into 3 manipulators, with additional micro-grippers and stereo microscope vision. The platform is capable of motion resolutions of 3 nm and an accuracy of approximately 1 µm [19]. The accuracy is sufficient for achieving automated assembly of compliant snap-fastener microparts.…”
Section: Description Of Assembly Cellmentioning
confidence: 99%
“…In past work [19], we have discussed aspects related to the yield of automated microassembly of compliant MEMS structures, and concluded that results are highly predictable under certain part design and robot accuracy conditions. In this paper we make use of the multi-robot microassembly cell µ³, located in our lab to configure a microspectrometer via hybrid assembly of silicon and glass sub-mm components.…”
Section: Introductionmentioning
confidence: 99%
“…Automated robotic microassembly is the final objective which is usually carried out by precise positioning [5], [6], [7] but it is not sufficient for all microassembly tasks [8]. Dual finger microgrippers with feedback are used to automate some microassembly tasks [6], [9].…”
Section: Introductionmentioning
confidence: 99%